An Examination of the Structural Stability of Bowman's Risk Return Paradox - Fiegenbaum, Avi (Institutional Knowledge at Singapore Management University, 1985)
The paper examines the dynamic behavior of Bowman's (1980, 1982) risk/return paradox. Using accounting risk measures it is demonstrated that the paradox is not stable across time or industries. Further, the paradox may disappear with market based risk measures. It is suggested that strategy researchers need to develop good ex-ante measures of risk.